2016
DOI: 10.5761/atcs.oa.16-00049
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Resection for Metastatic Gastric Cancer

Abstract: IntroductionPulmonary metastasectomy has come to be recognized as an effective treatment for selected patients with colorectal cancer, renal cancer and other malignancies, and in recent years, long-term survival after pulmonary metastasectomy has been reported in patients with several malignancies. [1][2][3] On the other hand, the role of pulmonary metastasectomy in gastric cancer patients with pulmonary metastasis is still unclear.The prognosis of patients with metastatic gastric cancer is poor. The median su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Figure 1 shows the study search strategy. Overall, 39 studies were included in the final review (26 for hepatic resection , 4 for pulmonary resection [44][45][46][47] and 9 for palliative gastrectomy [48][49][50][51][52][53][54][55] ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the study search strategy. Overall, 39 studies were included in the final review (26 for hepatic resection , 4 for pulmonary resection [44][45][46][47] and 9 for palliative gastrectomy [48][49][50][51][52][53][54][55] ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall survival outcomes are summarized in Table 3. Iijima et al [46] reported an overall 3-year survival rate of 30%. Kobayashi et al [47] showed a median survival time following pulmonary resection of 67 months and an overall 5-year survival rate of 59%, while Shiono et al [44] reported a value of 28%.…”
Section: Pulmonary Metastasis Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the present study also revealed that patients with single-site lung metastasis exhibited a favorable prognosis following resection of the metastatic lesion. Several retrospective studies reported a survival rate of nearly 30% at 5-years and improved prognosis for patients with advanced GC who underwent lung metastasis resection [30][31][32]. However, Sun et al suggested that the primary resection of GC with lung metastasis had no significant survival benefit [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have been published concerning favorable prognostic factors of pulmonary resection for gastric cancer. Iijima et al reported that early pathological stage of gastric cancer and absence of extrapulmonary metastasis were favorable prognostic factors [ 9 ]. Shiono et al reported that relatively good surgical outcome could be expected for patients with disease-free intervals longer than 12 months, and their observed 5-year survival rate of pulmonary metastasectomy was 28% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%